Cameroon : Third Review Under the Extended Credit Facility Arrangement and Requests for a Waiver of Nonobservance of a Performance Criterion and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report ;, 2018)
President Biya was re-elected as President of Cameroon on October 7 by a large margin, amidst some violence in anglophone regions. Growth is projected to gradually increase from 3.5 percent in 2017 to 3.8 percent in 2018, driven by construction activity ahead of the Africa Cup of Nations (CAN) and large infrastructure projects. Fiscal consolidation as of end-June was in line with program objectives, but faces significant headwinds in the second half of the year owing to accelerating capital spending and revenue shortfalls. The goods trade balance worsened significantly in H1 and private capital outflows increased, contributing to a slower-than-anticipated buildup of external buffers. The medium-term outlook remains positive with growth expected to increase to 4.4 percent in 2019 and reach 5 percent in the medium-term. Risks from heightened global uncertainty, insufficient adjustment at the regional level, and continued insecurity in the anglophone regions are increasing.